2020
DOI: 10.3390/nu12020361
|View full text |Cite
|
Sign up to set email alerts
|

Food Intervention with Folate Reduces TNF-α and Interleukin Levels in Overweight and Obese Women with the MTHFR C677T Polymorphism: A Randomized Trial

Abstract: Methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism associated with body fat accumulation could possibly trigger an inflammatory process by elevating homocysteine levels and increasing cytokine production, causing several diseases. This study aimed to evaluate the effects of food intervention, and not folate supplements, on the levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β) in overweight and obese women with the MTHFR C677T polymorphism. A randomized, dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…The MTHFR thermolabile variant encoded by the MTHFR 677 CT/TT genotypes leads to impaired homocysteine (Hcy) metabolism and elevated plasma Hcy levels, which has been associated with some metabolic diseases when coupled with insufficient dietary folate intake [10,11,54]. In particular, its association with accumulation of body and liver fat and increased risk of obesity have been explained by a possible mechanism in which elevated Hcy levels trigger an inflammatory process and increased production of cytokines, a metabolic feature that may cause insulin resistance, that later has been improved by a folate-rich diet [55]. Herein, the regionalized GENOMEX diet provided an adequate folate intake even higher than that usually consumed by individuals, and because the T allele was one of the most frequent among study subjects, it is plausible that the beneficial metabolic response was more evident compared to the other polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…The MTHFR thermolabile variant encoded by the MTHFR 677 CT/TT genotypes leads to impaired homocysteine (Hcy) metabolism and elevated plasma Hcy levels, which has been associated with some metabolic diseases when coupled with insufficient dietary folate intake [10,11,54]. In particular, its association with accumulation of body and liver fat and increased risk of obesity have been explained by a possible mechanism in which elevated Hcy levels trigger an inflammatory process and increased production of cytokines, a metabolic feature that may cause insulin resistance, that later has been improved by a folate-rich diet [55]. Herein, the regionalized GENOMEX diet provided an adequate folate intake even higher than that usually consumed by individuals, and because the T allele was one of the most frequent among study subjects, it is plausible that the beneficial metabolic response was more evident compared to the other polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally reviewed a number of studies reporting the levels of TNF-α across the different genotypes for other variants associated with different genes related with obesity and metabolic disorders [ 137 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ] ( Table S8 ). We also found a very high genotype intra-subgroup variability (CV% >40% in most cases), highly variable levels (0.11–90 pg/mL) in the homozygous reference subgroups, and small and mostly (NS) differences across the genotypes except for some specific SNPs.…”
Section: The Influence Of Genetic Variants On Tnf-α Levelsmentioning
confidence: 99%
“…Reduction of neurotransmitter levels due to inflammation is also thought to contribute to the development of syndromal symptoms of depression ( 14 ). Of note, higher dietary folate intake in obese/overweight women with the MTHFR C677T polymorphism, an indicator of elevated homocysteine levels and inflammation, has also been shown to reduce levels of inflammatory biomarkers, indicating that folate may play a role in the reduction of inflammation in the obese population ( 5 ).…”
Section: Inflammation and Depressionmentioning
confidence: 99%
“…Papakostas et al ( 1 ) first demonstrated that depressed patients with elevated body mass index (BMI) and inflammatory biomarkers responded particularly well to adjunctive LMF treatment. In subsequent years, additional data demonstrated the impact of elevated BMI and inflammation on depression and antidepressant response ( 2 , 3 ), as well as the potential for LMF to be an effective adjunctive treatment in this population ( 4 , 5 ). Because of the current interest on the effect of BMI and inflammation on major depressive disorder (MDD), these data will be revisited to provide additional context, potentially opening the door for additional investigation in this area.…”
Section: Introductionmentioning
confidence: 99%